Semantik Dalam Bahasa Indonesia - Nisaul Zahra; Yuni Sonia; Saida Adilla; Riski Ainaul Mardiyah; Dinda Amelia (Asosiasi Periset Bahasa Sastra Indonesia, 2024)
Semantics is defined as a field of linguistics that studies meaning. This includes semantic relationships or meaning relationships between language units, such as words, phrases, clauses, and sentences. Language units can be words, phrases, or sentences; and semantic relationships. In this study, the team of authors will discuss material related to semantics in language and technology. The purpose of this study is to provide new and in-depth knowledge related to the branch of linguistics, namely semantics in the realm of language and the development of the resulting technology.